Bibliography of Articles from Serial Publications on Serbian Female Musicians 1825−1914 (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Musical criticism in Serbia can be traced back to 1825. Amateurs and professional musicians, however, started showing increased interest in making music in the 1880s. Since there were still very few educated musicians in the late nineteenth century, many lawyers, teachers, doctors, priests, and politicians, as well as many other intellectuals or music lovers wrote musical reviews. Many of them were also amateur performers. Until World War I, there were also plenty female musicians in Serbia and some of them were internationally recognized. Most women who were musicians at the time are today forgotten or unknown in the public. This paper represents a bibliography of newspaper articles from 1825 to the beginning of the Great War in which women who were musicians in Serbia are mentioned.
Keywords: bibliography; Serbian female musicians; periodicals; musical articles